Plasma d-dimer levels increase with the severity of community acquired pneumonia. - (:unkn) unknown (My University, 2004)
The aim of this study is to investigate the relationship of the plasma D-Dimer (D-d) level and the severity of the pneumonia in patients who have not any disease that may increase the D-d level, but pneumonia. This is prospective controlled study. Using the ATS 2001 Community Acquired Pneumonia (CAP) Guideline we divided the patients into two groups [severe (n= 14) and non-severe (n= 37) CAP] and looked for any significant difference in D-d levels with ELISA method among the patients groups and control group. Plasma D-d levels were 2438 +/- 2158 ng/mL in severe CAP group, 912.6 +/- 512.6 ng/mL in non-severe CAP group and 387 +/- 99.56 ng/mL in the control group. Patients with non-severe CAP and those with severe CAP group both showed an increase in plasma levels of D-d compared to control group (p< 0.05, p< 0.001, respectively). We also found that the severe CAP group had increased in plasma levels of D-d compared to the non-severe CAP group (p< 0.001). Plasma D-d level increases significantly in patients with CAP compared to control group. Plasma D-d levels increases significantly with the severity of the CAP.